**Unformatted text preview: **+-= +-= + ∫ x a x x x a x dr r x r a Substitution yields the result . 1 2 2 2 2 +-= x a x a GMm F The second term in brackets can be written as 2 2 1 2 2 2 1 1 ) ) ( 1 ( ) ( 1 1 -≈ + = +-x a x a x a if x >> a , where the binomial approximation (or first-order Taylor series expansion) has been used. Substitution of this into the above form gives , 2 x GMm F ≈ as it should....

View
Full Document

- '
- NoProfessor
- Derivative, Power Series, Taylor Series, 2m, small ring exerts